SELF-HELP GROUP INTERVENTION TO IMPROVE DIETARY COMPLIANCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Enny Puspita; Ilmiatuz Zuhria; Roni Setiawan (PRIMA WIYATA HEALTH, 2026)
Background: Dietary non-compliance remains a major challenge in the management of patients with Type 2 Diabetes Mellitus (T2DM) and contributes to poor glycemic control and disease complications. Social support–based interventions, such as self-help groups, have been increasingly recognized as effective strategies to improve self-management behaviors among patients with chronic diseases. Objectives: This study aimed to examine the effect of a self-help group intervention on dietary compliance among patients with Type 2 Diabetes Mellitus. Methods: This study employed a pre-experimental one-group pretest–posttest design. A total of 60 patients with Type 2 Diabetes Mellitus who attended a primary health care center were selected using purposive sampling. Dietary compliance was measured using a structured questionnaire before and after the self-help group intervention. The intervention consisted of group education sessions, peer discussion, and mutual support activities. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. Results: Before the intervention, the majority of participants (85.0%) were categorized as non-compliant with dietary recommendations. After the self-help group intervention, dietary compliance significantly increased, with 78.3% of participants categorized as compliant. Statistical analysis showed a significant difference in dietary compliance before and after the intervention (p = 0.000). Conclusion: The self-help group intervention significantly improved dietary compliance among patients with Type 2 Diabetes Mellitus. This approach can be considered an effective and feasible strategy for diabetes management education in primary health care settings.